Forschungsschwerpunkte und Zukunftsaufgaben der Historischen Geographie: Industrie und Landwirtschaft - Krings, Wilfried (ERDKUNDE, 1982)
This contribution is concerned with the study of industry and agriculture within the context of historical geography in the area of the Federal Republic of Germany and during the period from the 18th century until 1945. Proceeding from research carried out so far and further aspects - present trends abroad (Great Britain, France, the Netherlands) in related disciplines and in cultural activities in general - four main tasks are formulated for the immediate future. First of all it is suggested that the cartographic presentation of past economic circumstances should be promoted. Secondly, it seems to be desirable to analyse the spatio-temporal development of partial aspects of agriculture and industry which have contributed to the modification of the old economic structures. Thirdly, it pleads for an increased usage of the social-geo graphical approach. Furthermore, information on historical elements and patterns in the landscape are now needed in order to support conservation measures. Fourthly, it is emphasized that methods and techniques ought to be available to historical geographers which would enable them to contribute successfully to the procurement of such information.